Клеточное размножение и процессы дифференциации - Андреева Л. Ф. (Проблемы биологии развития, 1983)
Экземпляры: КХ (20190422) / Инвентарный номер: 792137 / Сис.шифр: 576.3 / Авт.знак: К 48 / ГРНТИ: 34 / ББК: 28